The chemistry of milk and milk products physicochemical properties, therapeutic characteristics, and processing methods - Goyal, Megh R.; Ranvir, Suvartan; Malik, Junaid Ahmad, 1987- (Innovations in agricultural and biological engineering., 2024)
"This new volume aims to provide an understanding of the manufacturing processes of milk products and the structural, physicochemical, and compositional changes that occur during manufacturing and storage of milk products. It also addresses the various reactions that can happen during processing and storage of dairy products and their impact on quality. Milk and milk products are highly nutritious , yet their low acidity provides a favorable environment for growth of pathogenic and spoilage-causing organisms. Therefore milk needs to be processed and converted into various milk products. This volume covers methods of conversion of milk into high-value, concentrated, extended-shelf-life, and easily transportable dairy products. This volume covers the constituents and chemistry, physicochemical properties, and therapeutic characteristics of milk and milk products, and then goes on to present specialized processing methods for milk and milk products. It presents sound knowledge of raw milk composition, mineral constituents in milk, and manufacturing process of butter and ice cream. It also covers the physicochemical changes and compositional changes occurring during manufacturing and storage of milk, concentrated milk, butter, butter oil and ice cream. Also discussed are the therapeutic characteristics of fermented milk and milk products, milk-derived bioactive peptides, and potential aspects of whey proteins in dairy products. Specialized methods such as proteolysis in ultra-high temperature (UHT), heat and acid coagulation of milk products, processing and characteristics of dry dairy milk powders, and methods to monitor pesticide residues in milk and milk products have also been evaluated"